Global research landscape and trends of plant-based meat analogs: a bibliometric analysis - Yunting Xie; Linlin Cai; Guanghong Zhou; Chunbao Li (Food Materials Research)
Plant-based meat analogs have become an important topic in recent years. To scientifically understand the research situation of plant-based meat analogs, we analyzed 2,595 publications from January 2000 to October 2023 by bibliometric method based on the PubMed database. The results showed a gradual rise in the number of annual publications, with the fastest growth rate of 58.5% in 2021. The country with the most publications was the United States (685, 24.87%), followed by China (242, 8.79%) and the United Kingdom (196, 7.12%). The University of Helsinki, Texas A&M University and the University of California were core research institutions. Popular and important journals were mainly Foods, Nutrients, Meat Science, Food Research International, and Critical Reviews in Food Science and Nutrition. Current research topics focused on alternative proteins and their functional and nutritional characteristics, as well as sustainable development. The research interests have gradually expanded from quality characteristics to nutritional characteristics. Further improving the quality, controlling natural toxin contamination, as well as systematically investigating the effects on health were future research trends. The effects of plant-based meat analogs on metabolic pathways and diseases were important clues in the study of nutritional health. This bibliometric analysis comprehensively and quantitatively presents the research landscape and hotspots, and further suggests future research directions. These findings can benefit researchers in selecting appropriate journals and finding potential collaborators to achieve in-depth research in this field.